IMPLEMENTATION ANALYSIS OF INA-CBG's CLAIMS IMPLEMENTATION OF QUALITY CONTROL AND COST CONTROL AT TARUMAJAYA HOSPITAL, BEKASI IN 2021 - Taufiq; R. Fresley Hutapea; Muhammad Fachruddin Arrozi Adhikara (Syntax Corporation Indonesia, 2022)
The National Health Insurance whose implementation began in January 2014 made changes to the payment system from the Retrospective Paymant System to the Prospective Payment System with INA-CBG's rates. The implementation of JKN INA-CBG's is a fundamental problem so Tarumajaya Hospital Bekasi must make efforts to achieve quality and cost control. The purpose of this study was to determine the efforts taken by the hospital regarding the difference in outpatient service hospital rates with INA-CBG's rates. The research method was carried out quantitatively and qualitatively. The results of the study indicate that the implementation of JKN at Tarumajaya Hospital Bekasi has been carried out well, but there are still some things that are expected and must be improved. Human resources at Tarumajaya Hospital Bekasi in carrying out the JKN program are still not optimal in terms of quantity and quality, due to the lack of availability of human resources for specialist doctors, clinical pathology specialists, radiology specialists, urology specialists at Tarumajaya Hospital Bekasi is one of the problems faced and can hinder program implementation. JKN, even though it is really needed by the surrounding community because it is far from other health services and will affect the health services at Tarumajaya Hospital Bekasi. The facilities and infrastructure of the Tarumajaya Bekasi Hospital are still lacking in providing health services, including the availability of medical devices and facilities such as hemodialysis, special room facilities and operating rooms, only one is available, as well as the availability of rooms that are still limited so patients must be referred. External factors such as cross-sectoral roles are still less concerned with their role in JKN, seen from the role of the Regional Government which is difficult to meet because they are busy with other matters, as well as the Health Office because of the existence of JKN. if other problems have to deal with BPJS.